THE EFFECT OF PRICE FAIRNESS AND CAFÉ ATMOSPHERE ON CUSTOMER LOYALTY: THE MEDIATING ROLE OF PERCEIVED SATISFACTION (A STUDY AT RUTINITAS COFFEE SHOP IN SUKABUMI) - Maulana, Adrian; Arina Lestari, Nurni; Abdul Aziz, Muh (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the effect of perceived price fairness and café atmosphere on customer loyalty through customer satisfaction at coffee shops in Sukabumi City. The rapid growth of the coffee shop industry has intensified competition, requiring business owners to better understand factors that influence customer satisfaction and long-term loyalty. Perceived price fairness reflects customers’ evaluations of whether the prices charged are reasonable and proportional to the value received, while café atmosphere represents the physical and emotional environment experienced by customers, including interior design, music, lighting, and overall comfort. This research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to coffee shop consumers in Sukabumi City who have visited coffee shops more than once. The measurement instruments were designed using a Likert scale to capture respondents’ perceptions of price fairness, café atmosphere, customer satisfaction, and customer loyalty. The data analysis technique used in this study is Structural Equation Modeling (SEM) with AMOS, which allows for simultaneous testing of both direct and indirect relationships among the variables. SEM is applied to examine the effect of perceived price fairness and café atmosphere on customer satisfaction, as well as their impact on customer loyalty, both directly and through customer satisfaction as a mediating variable.